Implementasi Metode Pembelajaran Drill dengan Teknik Inquiry untuk Meningkatkan Aktivitas dan Hasil Belajar Siswa - Ariesma Andriyanti; Ria Herdhiana; Cucu Lisnawati (EDUCARE, 2013)
This research is motivated by the low activity and learning outcomes of students in accounting subjects. In accounting subjects students are expected to carry out learning activities so that they can influence student learning outcomes. In addition to understanding accounting is a subject that requires special expertise that must be practiced. The material chosen is journal material, because the journal is the basis for making the next financial report. A teacher must be able to create learning that can facilitate the creation of student learning activities. In this study used Drill Learning Method with Inquiry Technique. The method used is the experimental method, while the nature of the research used in this research is quantitative research. The results showed that the use of the method in the learning activities is important, therefore teachers should be able to choose, design and implement learning method in accordance with the characteristics of the subjects, the students 'characteristics, the characteristics of the learning objectives so as to create an atmosphere of learning that can facilitate the students' learning activities and can help improve student learning outcomes.